The Role of Nanovaccine in Cross-Presentation of Antigen-Presenting Cells for the Activation of CD8+ T Cell Responses - Cheol Gyun Kim; Yoon-Chul Kye; Cheol-Heui Yun (MDPI AG, 2019)
Explosive growth in nanotechnology has merged with vaccine development in the battle against diseases caused by bacterial or viral infections and malignant tumors. Due to physicochemical characteristics including size, viscosity, density and electrostatic properties, nanomaterials have been applied to various vaccination strategies. Nanovaccines, as they are called, have been the subject of many studies, including review papers from a material science point of view, although a mode of action based on a biological and immunological understanding has yet to emerge. In this review, we discuss nanovaccines in terms of CD8+ T cell responses, which are essential for antiviral and anticancer therapies. We focus mainly on the role and mechanism, with particular attention to the functional aspects, of nanovaccines in inducing cross-presentation, an unconventional type of antigen-presentation that activates CD8+ T cells upon administration of exogenous antigens, in dendritic cells followed by activation of antigen-specific CD8+ T cell responses. Two major intracellular mechanisms that nanovaccines harness for cross-presentation are described; one is endosomal swelling and rupture, and the other is membrane fusion. Both processes eventually allow exogenous vaccine antigens to be exported from phagosomes to the cytosol followed by loading on major histocompatibility complex class I, triggering clonal expansion of CD8+ T cells. Advancement of nanotechnology with an enhanced understanding of how nanovaccines work will contribute to the design of more effective and safer nanovaccines.